Develop and Usable a Warfarin Mobile App with no-Code and Free: New Case Drug Management - Thungwilai, Worawit; Pamonsinlapatham , Perayot (Region 3 Medical and Public Health Journal - วารสารวิชาการแพทย์และสาธารณสุข เขตสุขภาพที่ 3, 2025)
Objectives: 1. To develop a medication tracking and patient care system through a no-code mobile application. 2. To promote medication adherence among patients. 3. To assess patient satisfaction with the mobile application. Methods: This study was conducted among new warfarin users in the internal medicine and stroke wards at Sawanpracharak Hospital between July and August 2023. Patients were divided into two groups, each comprising 30 participants. The control group received standard medication counseling from pharmacists, while the experimental group received the same counseling plus medication tracking via the mobile application. Follow-up was conducted twice, to evaluate INR values, medication adherence, and application satisfaction. Results: In the control group, the percentage of patients with INR values within the target range at the two follow-ups was 26.67% and 33.33%, respectively. In the experimental group, it was 90.00% and 96.67%, respectively. No severe adverse events were reported in either group. The experimental group had a lower INR variance than the control group (0.08 vs. 2.69, respectively). Chi-square testing showed that patients in the experimental group were significantly more likely to have INR values within the target range than those in the control group (p-value<0.05). Application satisfaction was rated as good, with scores exceeding 4.0 out of 5.0 across all categories. The findings suggest that mobile applications improved medication adherence and helped patients achieve target INR values from the first follow-up. Conclusion: The no-code mobile application developed in this study effectively tracked warfarin use and represents a new option for individuals without a technology background who wish to create practical tools. Keywords: Warfarin, Mobile Application, No-Code, Thunkable, Medication Adherence